Soil C and N availability determine the priming effect: microbial N mining and stoichiometric decomposition theories - Chen, Ruirui; Senbayram, Mehmet; Blagodatsky, Sergey; Myachina, Olga; Dittert, Klaus; Lin, Xiangui; Blagodatskaya, Evgenia; Kuzyakov, Yakov (Global change biology, 2014)
The increasing input of anthropogenically derived nitrogen (N) to ecosystems raises a crucial question: how does available N modify the decomposer community and thus affects the mineralization of soil organic matter (SOM). Moreover, N input modifies the priming effect (PE), that is, the effect of fresh organics on the microbial decomposition of SOM. We studied the interactive effects of C and N on SOM mineralization (by natural ¹³C labelling adding C₄‐sucrose or C₄‐maize straw to C₃‐soil) in relation to microbial growth kinetics and to the activities of five hydrolytic enzymes. This encompasses the groups of parameters governing two mechanisms of priming effects – microbial N mining and stoichiometric decomposition theories. In sole C treatments, positive PE was accompanied by a decrease in specific microbial growth rates, confirming a greater contribution of K‐strategists to the decomposition of native SOM. Sucrose addition with N significantly accelerated mineralization of native SOM, whereas mineral N added with plant residues accelerated decomposition of plant residues. This supports the microbial mining theory in terms of N limitation. Sucrose addition with N was accompanied by accelerated microbial growth, increased activities of β‐glucosidase and cellobiohydrolase, and decreased activities of xylanase and leucine amino peptidase. This indicated an increased contribution of r‐strategists to the PE and to decomposition of cellulose but the decreased hemicellulolytic and proteolytic activities. Thus, the acceleration of the C cycle was primed by exogenous organic C and was controlled by N. This confirms the stoichiometric decomposition theory. Both K‐ and r‐strategists were beneficial for priming effects, with an increasing contribution of K‐selected species under N limitation. Thus, the priming phenomenon described in ‘microbial N mining’ theory can be ascribed to K‐strategists. In contrast, ‘stoichiometric decomposition’ theory, that is, accelerated OM mineralization due to balanced microbial growth, is explained by domination of r‐strategists.